2022
DOI: 10.1186/s12977-022-00604-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 genome editing to create nonhuman primate models for studying stem cell therapies for HIV infection

Abstract: Nonhuman primates (NHPs) are well-established basic and translational research models for human immunodeficiency virus (HIV) infections and pathophysiology, hematopoietic stem cell (HSC) transplantation, and assisted reproductive technologies. Recent advances in CRISPR/Cas9 gene editing technologies present opportunities to refine NHP HIV models for investigating genetic factors that affect HIV replication and designing cellular therapies that exploit genetic barriers to HIV infections, including engineering m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…The incidence of chromothripsis was not assessed in the present study given the limitations in interpreting WGA artifacts in light of an incomplete reference genome, in addition to the difficulty in discerning whether chromosome loss was due to CRISPR-Cas9 targeting or naturally-occurring cellular fragmentation events. As CRISPR-Cas9 editing errors can result in chromosomal disruption and/or elimination ( Leibowitz et al, 2021 ; Papathanasiou et al, 2021 ) it is plausible that the embryo development may be negatively impacted and could explain the poor embryo transfer rate observed in our previous study ( Schmidt et al, 2020 ) and in general the low live birth rates of CRISPR-Cas9 targeted NHPs ( Schmidt et al, 2022a ; Schmidt et al, 2022b ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The incidence of chromothripsis was not assessed in the present study given the limitations in interpreting WGA artifacts in light of an incomplete reference genome, in addition to the difficulty in discerning whether chromosome loss was due to CRISPR-Cas9 targeting or naturally-occurring cellular fragmentation events. As CRISPR-Cas9 editing errors can result in chromosomal disruption and/or elimination ( Leibowitz et al, 2021 ; Papathanasiou et al, 2021 ) it is plausible that the embryo development may be negatively impacted and could explain the poor embryo transfer rate observed in our previous study ( Schmidt et al, 2020 ) and in general the low live birth rates of CRISPR-Cas9 targeted NHPs ( Schmidt et al, 2022a ; Schmidt et al, 2022b ).…”
Section: Discussionmentioning
confidence: 89%
“…Transplantation of hematopoietic stem cells (HSCs) containing the CCR5 -Δ32 mutation to human HIV patients led to the cure of HIV infection in some but not all cases ( Hütter et al, 2009 ; Allers et al, 2011 ; Henrich et al, 2014 ; Cummins et al, 2017 ). Generating NHPs with CCR5 -deletions would aid in determining the mechanisms of HIV elimination following transplantation of allogeneic HSCs with CCR5 mutations and the development of clinical protocols for reproducible HIV cure ( Schmidt et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of morphokinetic analysis enables the quantification of differences in timing of developmental events to assess the impact of experimental manipulation such as genome editing, gene knockdown, or experimental infection during this developmental time frame. Recent research has focused on developing nonhuman primate genetic models of human disease through genome editing of embryos [31, 32], yet the impact that CRISPR-Cas9 on- and off-target editing has on early embryo development remains uncertain. Time-lapse imaging could be used to deselect embryos for transfer that have had an atypical cleavage pattern, although no differences were observed in this study between blastocysts with normal or abnormal cleavage patterns in their ability to attach to an extracellular matrix and grow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nanoparticle‐mediated CRISPR/Cas9‐encoding mRNA delivery is the most frequently used gene‐editing technology (Figure 3). Several studies have shown that in non‐human primate models, CRISPR/Cas9‐mediated CCR5 disruption is used to give resistance to HIV/SIV infection 144 . Therefore, mRNA‐based genome editing will be a promising modality for gene therapy, and several of them are undergoing clinical studies.…”
Section: Mrna For Therapeutic Applicationsmentioning
confidence: 99%
“…Several studies have shown that in non‐human primate models, CRISPR/Cas9‐mediated CCR5 disruption is used to give resistance to HIV/SIV infection. 144 Therefore, mRNA‐based genome editing will be a promising modality for gene therapy, and several of them are undergoing clinical studies.…”
Section: Mrna For Therapeutic Applicationsmentioning
confidence: 99%